Cytotoxic activity of Holothuria tubulosa (Echinodermata) coelomocytes. Issue 72 (January 2018) - Vazzana, Mirella; Celi, Monica; Chiaramonte, Marco; Inguglia, Luigi; Russo, Debora; Ferrantelli, Vincenzo; Battaglia, Dominique; Arizza, Vincenzo
Abstract: The immune system of marine invertebrates, in particular that of holothurians, still requires further study. Our research showed that coelomocyte cells contained in the coelomic fluid of the sea cucumber, Holothuria tubulosa, are able to lyse, in vitro, red blood cells in rabbits and sheep. A plaque-forming assay showed spherule cells to be the effector cells, able to release cytotoxic molecules after xenogenic cell contact. The coelomocyte lysate supernatant, analysed by polyacrylamide gel electrophoresis overlay technique, using rabbit and sheep erythrocytes, showed two different haemolytic protein patterns: one calcium dependent and the other calcium independent. The fractions of each pattern were resolved on a polyacrylamide gel and calcium-dependent and independent coelomocyte lysate patterns were compared. Highlights: Coelomocytes of Holothuria tubulosa, are able to lyse, in vitro, red blood cells in rabbits and sheep. Coelomocytes are able to release cytotoxic molecules after xenogenic cell contact causing plaque lysis. Cytotoxic molecules are proteins showing a different lysis pattern in presence or in absence of calcium ions.